1999
DOI: 10.1146/annurev.ento.44.1.159
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens and Predators of Ticks and Their Potential in Biological Control

Abstract: This review summarizes the literature about pathogens and predators of ticks and their potential use as biocontrol agents published since the beginning of this century. In nature, many bacteria, fungi, spiders, ants, beetles, rodents, birds, and other living things contribute significantly toward limiting tick populations, as do, for instance, the grooming activities of hosts. Experiments with the most promising potential tick biocontrol agents--especially fungi of the genera Beauveria and Metarhizium and nema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(133 citation statements)
references
References 99 publications
0
128
0
5
Order By: Relevance
“…This result implies that wet summers might actually prove detrimental to immature blacklegged ticks, perhaps by enhancing the abundance or efficacy of natural enemies. Entomopathogenic soil fungi (Metarhizium and Beauveria), which seem capable of controlling blacklegged tick populations under some conditions (Samish andRehacek 1999, Benjamin et al 2002), might benefit from high summer precipitation and subsequently might reduce tick abundance. Recently, Chase and Knight (2003) found that wet conditions supported predators and competitors capable of reducing wetland mosquito populations, with the surprising result that mosquito populations were more abundant following dry than wet years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result implies that wet summers might actually prove detrimental to immature blacklegged ticks, perhaps by enhancing the abundance or efficacy of natural enemies. Entomopathogenic soil fungi (Metarhizium and Beauveria), which seem capable of controlling blacklegged tick populations under some conditions (Samish andRehacek 1999, Benjamin et al 2002), might benefit from high summer precipitation and subsequently might reduce tick abundance. Recently, Chase and Knight (2003) found that wet conditions supported predators and competitors capable of reducing wetland mosquito populations, with the surprising result that mosquito populations were more abundant following dry than wet years.…”
Section: Discussionmentioning
confidence: 99%
“…Based on Subak (2003) and Jones and Kitron (2000), we expected a priori that Lyme disease risk would be positively correlated with each of these weather variables except TSP1. High TSP1 could enhance Lyme disease risk by reducing desiccation of larval ticks, but it could also possibly foster fungi and other natural enemies of ticks (Samish and Rehacek 1999). Unlike acorn and mouse 6 ͗http://www.ncdc.noaa.gov/oa/climate/climatedata.html͘ data, which were recorded at a single Dutchess County site, weather data were available for each state individually ( Fig.…”
Section: Weather Datamentioning
confidence: 99%
“…Shrews seem to locate hidden ticks by their smell. Mice and rats are often cited as preying on ticks [39]. However, it is worth to mention here that it is not advisable to use rodents for controlling insects as they are more harmful and transmit more diseases than insects.…”
Section: Rodents and Mammalsmentioning
confidence: 99%
“…fungus, entomogenous nematodes, vegetal extracts, volatile oils, etc.) (Borges et al, 2011;Chagas de Souza et al, 2012;Kaaya et al, 1996;Kaaya et al, 2000;Jongejan and Uilenberg, 1994;Samish and Rehacek, 1999;Zahir and Rahuman, 2012).…”
Section: Introductionmentioning
confidence: 99%